2022
DOI: 10.1177/27539687221117836
|View full text |Cite
|
Sign up to set email alerts
|

Reworking the political in digital forests: The cosmopolitics of socio-technical worlds

Abstract: Forests are increasingly central to policies and initiatives to address global environmental change. Digital technologies have become crucial components of these projects as the tools and systems that would monitor and manage forests for storing carbon, preserving biodiversity, and providing ecosystem services. Historically, technologies have been instrumental in forming forests as spaces of conservation, extraction, and inhabitation. Digital technologies build on previous techniques of forest management, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 160 publications
0
9
0
Order By: Relevance
“…The regulation of nonhuman environments is increasingly digitised, following wider trends in technological innovation (Gabrys et al 2022; Goldstein and Nost 2022, 59). Social scientists question the authority transferred to digital technologies, as devices like drones take on new roles in ‘automated’ decision-making pathways – a process that Adams (2019) terms ‘algorithmic’ governance.…”
Section: Decision-making: Conservation Technologies and Digital Ecolo...mentioning
confidence: 99%
See 2 more Smart Citations
“…The regulation of nonhuman environments is increasingly digitised, following wider trends in technological innovation (Gabrys et al 2022; Goldstein and Nost 2022, 59). Social scientists question the authority transferred to digital technologies, as devices like drones take on new roles in ‘automated’ decision-making pathways – a process that Adams (2019) terms ‘algorithmic’ governance.…”
Section: Decision-making: Conservation Technologies and Digital Ecolo...mentioning
confidence: 99%
“…One thing that is clear within our analysis is that the use of drones as part of surveillance infrastructures is especially relevant in what we may call ‘state’ landscapes: productions of more-than-human ecologies in which conservation plays a primarily disciplinary or biopolitical role (Peluso and Vandergeest 2011). State forests are primarily administrative entities, which function to legitimise some visions and actors over others, while extending state powers to organise and regulate populations (Gabrys et al 2022). This administrative organising is articulated with environmental scientific knowledge, especially forestry engineering, to calculate and measure the amount of forest and give it a monetizable value that again justifies the counterinsurgency advance to remove the armed groups in the area (Peluso 1991).…”
Section: Differential Implications Of Using Drones In Biodiversity Co...mentioning
confidence: 99%
See 1 more Smart Citation
“…Digital operations and practices facilitating the datafication, automation and optimisation of forest environments produce temporalities oriented around newness, liveness, linearity, accumulation, simultaneity, and efficiency (Gabrys et al, 2022). In this context, the real-time has emerged as a technological and temporal paradigm for smart environmental monitoring and regulation (Bakker and Ritts, 2018;Gabrys, 2016 ).…”
Section: Real-time Forestsmentioning
confidence: 99%
“…Data practices and data sciences then contribute to different social-political effects, depending upon who is involved in using digital technologies, generating data, and acting on evidence. As the Smart Forests research project has demonstrated, power inequalities can arise across actors such as big tech companies in the Global North and forest communities in the Global South, or across environmental policymakers and commercial tech firms with different objectives and commitments to addressing environmental change (Gabrys et al 2022). The "datafication" of forest environments involves selecting, mobilising, and sustaining particular forest worlds, which can come at the expense of others.…”
Section: Smart Forestsmentioning
confidence: 99%